Balloon Assisted Endovascular Coiling in Wide Neck Basilar Tip Aneurysm - Inayat Ali Khan; Irfan Lutfi; Muhammad Ali; Atiq Ahmed Khan (ziauddin University, 2024)
Basilar tip aneurysms are the commonest aneurysms of the posterior circulation and constitute around 5-8% of all cerebral aneurysms. Ruptured basilar tip aneurysms may present with signs and symptoms of subarachnoid hemorrhage (SAH) with sudden, extremely severe headache, nausea and vomiting, stiff neck, blurred or double vision, sensitivity to light, seizure, drooping eyelid and loss of consciousness. At times, the hemorrhage could be fatal, reaching mortality beyond 20%. Basilar tip aneurysms have complex anatomy and have always been considered difficult to treat. Two well-known options to treat basilar tip aneurysms include the microsurgical approach and the endovascular approach. Endovascular treatment is now a cost-effective, preferred and logical rationale for the management of intracranial aneurysms. This case reports the first ever coiling procedure that was performed at Ziauddin Hospital (North Campus) for a basilar tip aneurysm and the other major challenge faced at our center was that the neck was wide, hence requiring a supporting balloon. Keywords: Aneurysm; Subarachnoid Hemorrhage; Cerebral Aneurysms.